FEER for the CFA Franc - Tsangarides, Charalambos (IMF Working Papers; Working Paper ;, 2006)
We apply the fundamentals equilibrium exchange rate (FEER) approach and the Johansen cointegration methodology to investigate the behavior of the real effective exchange rates of the two monetary unions of the CFA franc zone (CEMAC and WAEMU) vis-a-vis their long-run equilibrium paths. For both CEMAC and WAEMU, our results indicate that: (i) the fundamentals account for most of the fluctuation of the real effective exchange rates, with increases in the terms of trade, government consumption, and productivity improvements causing the exchange rate to appreciate, and increases in investment and openness leading to a depreciation; (ii) at end-2005 both the CEMAC and WAEMU real effective exchange rates were broadly in line with their long-run equilibrium values; and (iii) following a shock, reversion to equilibrium is twice as fast in WAEMU than in CEMAC.